A systematic review and network meta-analysis of randomised controlled trials comparing neoadjuvant treatment strategies for stage II and III rectal cancer. (March 2023) - Simillis, Constantinos; Khatri, Amulya; Dai, Nick; Afxentiou, Thalia; Jephcott, Catherine; Smith, Sarah; Jadon, Rashmi; Papamichael, Demetris; Khan, Jim; Powar, Michael P.; Fearnhead, Nicola S.; Wheeler, James; et al.
Abstract: Aim: Multiple neoadjuvant therapy strategies have been used and compared for rectal cancer and there has been no true consensus as to the optimal neoadjuvant therapy regimen. The aim is to identify and compare the neoadjuvant therapies available for stage II and III rectal cancer. Design: A systematic literature review was performed, from inception to August 2022, of the following databases: MEDLINE, EMBASE, Science Citation Index Expanded, Cochrane Library. Only randomized controlled trials comparing neoadjuvant therapies for stage II and III rectal cancer were considered. Stata was used to draw network plots, and a Bayesian network meta-analysis was conducted through models utilizing the Markov Chain Monte Carlo method in WinBUGS. Results: A total of 58 articles were included based on 41 randomised controlled trials, reporting on 12, 404 participants that underwent 15 neoadjuvant treatment regimens. No significant difference was identified between treatments for major or total postoperative complications, anastomotic leak rates, or sphincter-saving surgery. Straight to surgery (STS) ranked as best treatment for preoperative toxicity but ranked worst treatment for positive resection margins and complete response. STS had significantly increased positive resection margins compared to long-course chemoradiotherapy with short-wait (LCCRT-SW) or long-wait (LCCRT-LW) to surgery, or short-course radiotherapy with short-wait (SCRT-SW) or immediate surgery (SCRT-IS). LCCRT-SW or LCCRT-LW resulted in significantly increased complete response rates compared to STS. LCCRT-LW significantly improved 2-year overall survival compared to STS, SCRT-IS, SCRT-SW. Total neoadjuvant therapy regimes with short-course radiotherapy followed by consolidation chemotherapy (SCRT-CT-SW), induction chemotherapy followed by long-course chemoradiotherapy (CT-LCCRT-S), long-course chemoradiotherapy followed by consolidation chemotherapy (LCCRT-CT-S), significantly improved positive resection margins, complete response, and disease-free survival compared to STS. Chemotherapy with monoclonal antibodies followed by long-course chemoradiotherapy (CT+MAB-LCCRT+MAB-S) significantly improved complete response and positive resection margins compared to STS, and 2-year disease-free survival compared to STS, SCRT-IS, SCRT-SW, SCRT-CT-SW, LCCRT-SW, LCCRT-LW. CT+MAB-LCCRT+MAB-S ranked as best treatment for disease-free survival and overall survival. Conclusions: Conventional neoadjuvant therapies with short-course radiation or long-course chemoradiotherapy have oncological benefits compared to no neoadjuvant therapy without increasing perioperative complication rates. Prolonged wait to surgery may improve oncological outcomes. Total neoadjuvant therapies provide additional benefits in terms of complete response, positive resection margins, and disease-free survival. Monoclonal antibody therapy may further improve oncological outcomes but currently is only applicable to a small subgroup of patients and requires further validation. Highlights: Neoadjuvant therapy does not significantly increase perioperative complications. Short-course radiation or long-course chemoradiation improve oncological outcomes. Prolonged wait to surgery improves outcomes without increasing complications. Total neoadjuvant therapy improves complete response rate and disease-free survival. Monoclonal antibodies may improve oncological outcomes but not widely applicable.